Low temperature curing lubricating coating for fan bearing and preparation method thereof

By modifying the mixed powder of molybdenum disulfide and polytetrafluoroethylene in low-temperature curing lubricating coating for fan bearings, the dry friction problem of fan gearbox bearings in the early stage of starting and the problems of traditional liquid lubricating high curing temperature are solved, and the problem of high curing temperature of traditional liquid lubricating is achieved. The effects of high adhesion, wear resistance and lubricating properties protect the bearing structure and extend the service life of the equipment.

CN119119838BActive Publication Date: 2025-02-21XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411610524.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The dry friction of fan gearbox bearings in the early stage of starting cause the surface is extremely vulnerable to damage. Traditional liquid lubrication has high curing temperature problems, which leads to oxidation and discoloration of the bearings. The surface of the lubricating material lacks active groups, which has poor compatibility, which affects the density of the coating. , lubricity and wear resistance.

Method used

Provide a low-temperature curing lubricating coating for fan bearings, containing mixed solvents, composite bonding resins, modified lubricating fillers, wear-resistant fillers, dispersants, micronized dicyandiamide, leveling agents, defoaming agents and anti-deposition agents. The interface compatibility of the lubricating filler with other components is improved by modifying the mixed powder of molybdenum disulfide and polytetrafluoroethylene.

Benefits of technology

It improves the adhesion, wear resistance and lubricating properties of lubricating coatings, protects the structural mechanics of the bearings, reduces the curing temperature, avoids oxidation and discoloration, and improves the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119838B_ABST
    Figure CN119119838B_ABST
Patent Text Reader

Abstract

The present disclosure relates to the technical field of lubricating coatings, and specifically to a low-temperature curing lubricating coating for fan bearings and a preparation method thereof. The lubricating coating comprises the following components by weight: 55-65 parts of a mixed solvent, 10-15 parts of a composite bonding resin, 10-15 parts of a modified lubricating filler, 8-12 parts of a wear-resistant filler, 0.5-3 parts of a dispersant, 0.5-1 parts of micronized dicyandiamide, 0.5-2 parts of a leveling agent, 0.5-2 parts of a defoamer, and 0.5-1 parts of an anti-settling agent; wherein the composite bonding resin comprises the following components by weight: 10-20 parts of an organic silicone resin, 15-30 parts of a phenolic epoxy resin, 15-30 parts of a polyurethane acrylate, and 35-45 parts of a polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene. The present disclosure can improve the adhesion, wear resistance, and lubrication performance of the lubricating coating and reduce the curing temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present disclosure relate to the technical field of lubricating coatings, and in particular, to a low-temperature curing lubricating coating for a fan bearing and a method for preparing the low-temperature curing lubricating coating for a fan bearing. Background Art

[0002] In the context of the global low-carbon economy, the proportion of wind energy in the energy structure continues to increase. Gearbox bearings are essential components in wind turbines. During the operation of the wind turbine, the wind wheel is subjected to extremely harsh stress conditions. It often runs for dozens of hours under rapidly changing heavy loads. All the loads it is subjected to are directly transmitted to the low-speed shaft of the gearbox through the main shaft. In order to protect the gearbox bearings, lubricating oil is usually added during operation. The lubrication effect of the oil film can effectively reduce mechanical wear and increase the service life of the equipment. However, in the early stage of equipment startup, it is difficult for the oil film to evenly cover the bearing surface, and dry friction in a short period of time causes the bearing surface to be easily damaged.

[0003] Compared with traditional liquid lubrication, solid lubricating coatings are suitable for dry film lubrication and have become the first choice for solving dry friction damage to wind turbine gearbox bearings. However, high-performance lubricating coatings in related technologies mainly use polyethersulfone, polyimide, etc. as film-forming materials, and the curing temperature is higher than 200°C. High-temperature treatment can easily cause oxidation and discoloration of bearings. In addition, due to the lack of active groups on the surface of current lubricating materials and poor compatibility with other inorganic fillers and organic resins, the coating's compactness, lubricity, wear resistance and other properties are impaired. Summary of the invention

[0004] The purpose of the present disclosure is to provide a low-temperature curing lubricating coating for fan bearings and a method for preparing the low-temperature curing lubricating coating for fan bearings, thereby improving the adhesion, wear resistance and lubrication performance of the lubricating coating at least to a certain extent, effectively protecting the structural mechanics of the bearing body, and avoiding oxidation discoloration of the bearing body due to high-temperature treatment.

[0005] According to one aspect of the present disclosure, a low-temperature curing lubricating coating for a fan bearing is provided, which comprises the following components in parts by weight: 55-65 parts of a mixed solvent, 10-15 parts of a composite adhesive resin, 10-15 parts of a modified lubricating filler, 8-12 parts of a wear-resistant filler, 0.5-3 parts of a dispersant, 0.5-1 parts of micronized dicyandiamide, 0.5-2 parts of a leveling agent, 0.5-2 parts of a defoaming agent, and 0.5-1 parts of an anti-settling agent; wherein the composite adhesive resin comprises the following components in parts by weight: 10-20 parts of an organosilicon resin, 15-30 parts of a phenolic epoxy resin, 15-30 parts of a polyurethane acrylate, and 35-45 parts of a polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene.

[0006] In an exemplary embodiment of the present disclosure, the mixed solvent includes the following components in parts by weight: 35-45 parts of xylene, 1-5 parts of n-butyl acetate, 15-25 parts of ethylene glycol ethyl ether acetate, 20-30 parts of 2-butoxyethanol, 1-5 parts of benzyl alcohol, 5-10 parts of n-butanol, and 1-3 parts of 2-propanol.

[0007] In an exemplary embodiment of the present disclosure, the wear-resistant filler includes aluminum tripolyphosphate, fumed silica and titanium dioxide, and the weight ratio between the aluminum tripolyphosphate, the fumed silica and the titanium dioxide is 1:2:2.

[0008] In an exemplary embodiment of the present disclosure, a modified lubricating filler is prepared by the following steps: molybdenum disulfide and polytetrafluoroethylene are mixed in a preset mass ratio to obtain a mixed powder comprising molybdenum disulfide and polytetrafluoroethylene, and the mixed powder is treated by dielectric barrier discharge plasma technology; the treated mixed powder is ultrasonically dispersed in an ethanol solution, a preset mass of a modifier is added, the mixture is reacted at room temperature for 8 to 24 hours, and then the modified lubricating filler is obtained after centrifugation, washing and drying.

[0009] In an exemplary embodiment of the present disclosure, the preset mass ratio is that the mass ratio of molybdenum disulfide to polytetrafluoroethylene is 1:1~4:1.

[0010] In an exemplary embodiment of the present disclosure, the particle size of molybdenum disulfide is 3-7 μm, and the particle size of polytetrafluoroethylene is 500 nm-3 μm.

[0011] In an exemplary embodiment of the present disclosure, the discharge gap width of the dielectric barrier discharge plasma technology is 8 mm, the voltage is 30 kV, the gas flow rate is 20-50 mL / min, the gas is a mixture of oxygen and water vapor obtained by bubbling, and the treatment time is 4-8 h.

[0012] In an exemplary embodiment of the present disclosure, the modifier is a combination of a first modifier, a second modifier and a third modifier; wherein the addition amount of the first modifier is 3% to 5% of the total mass of the mixed powder containing molybdenum disulfide and polytetrafluoroethylene, the addition amount of the second modifier is 1% to 2% of the total mass of the powder, and the addition amount of the third modifier is 0.2% to 0.5% of the total mass of the powder.

[0013] In an exemplary embodiment of the present disclosure, the first modifier is selected from a silane coupling agent modifier, the second modifier is selected from a thiol-containing modifier having the following structure, and the third modifier is selected from dodecyltrimethylammonium chloride,

[0014]

[0015] Wherein, m and n are independent of each other, n is a natural number selected from 3 to 5, and m is a natural number selected from 1 to 3.

[0016] According to one aspect of the present disclosure, a method for preparing a low-temperature curing lubricating coating for a fan bearing is provided, comprising: adding a composite bonding resin to a mixed solvent, and after the composite bonding resin is completely dissolved, fully dispersing a modified lubricating filler in the mixed solvent, and adding a dispersant and a defoaming agent and stirring to obtain a uniform slurry; wherein the composite bonding resin comprises the following components in parts by weight: 10 to 20 parts of an organic silicone resin, 15 to 30 parts of a phenolic epoxy resin, 15 to 30 parts of a polyurethane acrylate, and 35 to 45 parts of a polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene; wear-resistant fillers and micronized dicyandiamide are sequentially added to the uniform slurry, stirred evenly, ball-milled and dispersed, and filtered to obtain a filtered slurry; a leveling agent, a defoaming agent, and an anti-settling agent are sequentially added to the filtered slurry and stirred to prepare a low-temperature curing lubricating coating for a fan bearing.

[0017] In the technical solution provided in the embodiment of the present disclosure, a lubricating coating comprising a mixed solvent, a composite bonding resin, a modified lubricating filler, a wear-resistant filler, a dispersant, a micronized dicyandiamide, a leveling agent, a defoaming agent and an anti-settling agent is provided. The modified lubricating filler obtained by modifying a mixed powder comprising molybdenum disulfide and polytetrafluoroethylene can effectively improve the interfacial compatibility between the lubricating filler and the remaining components of the coating, making the lubricating coating structure compact. The provided composite bonding resin has the characteristics of high hardness, good wear resistance and low surface friction coefficient, and can effectively improve the wear resistance and lubrication performance of the lubricating coating. The provided composite bonding resin includes a polyhydroxy polyether resin including a large number of hydroxyl groups and has excellent adhesion to the surface of the substrate, thereby improving the adhesion of the lubricating coating. The provided mixed solvent has excellent solubility and wettability to the composite bonding resin and filler, and can promote curing, promote leveling, and enhance adhesion, thereby improving the adhesion, wear resistance and lubrication performance of the lubricating coating as a whole, and can effectively protect the structural mechanics of the bearing body. Moreover, compared with related technologies, the curing temperature of the lubricating coating can be lowered, thereby avoiding oxidation discoloration caused by high-temperature treatment of the wind turbine gearbox bearing.

[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0020] Figure 1 A schematic diagram shows a lubricating coating of Example 3 in the embodiments of the present disclosure after undergoing a Taber wear test.

[0021] Figure 2 A friction coefficient test diagram of a lubricating coating of Example 2 in the embodiments of the present disclosure is schematically shown.

[0022] Figure 3 A test diagram of the friction coefficient of the lubricating coating of Comparative Example 2 in the embodiment of the present disclosure is schematically shown.

[0023] Figure 4 A diagram schematically shows an adhesion test of a lubricating coating of Example 2 in the embodiments of the present disclosure.

[0024] Figure 5 The adhesion test diagram of the lubricating coating of comparative example 1 in the embodiment of the present disclosure is schematically shown.

[0025] Figure 6 The adhesion test diagram of the lubricating coating of comparative example 4 in the embodiment of the present disclosure is schematically shown.

[0026] Figure 7 An electron microscope image of a lubricating coating of Example 1 in the embodiments of the present disclosure is schematically shown.

[0027] Figure 8 An electron microscope image of a lubricating coating of Comparative Example 1 in the embodiments of the present disclosure is schematically shown.

[0028] Fig. 9 An electron microscope image of a lubricating coating of Comparative Example 3 in the embodiments of the present disclosure is schematically shown.

[0029] Fig.10 A diagram schematically shows the coefficient of friction of a plurality of mixed resin coatings in an embodiment of the present disclosure.

[0030] Fig.11 A schematic diagram schematically illustrates the micro-Vickers hardness and wear loss of each mixed resin coating in an embodiment of the present disclosure.

[0031] Fig.12 A schematic diagram schematically shows a method of testing the dry state of the coating surface of Example 1 using the finger touch method in an embodiment of the present disclosure.

[0032] Fig.13 A schematic diagram schematically shows the micro-Vickers hardness and friction coefficient of the coating corresponding to the lubricating coating of Example 1 in the embodiments of the present disclosure obtained at different curing temperatures.

[0033] Fig.14 The schematic diagram schematically shows the results of a tin bronze substrate after being treated at different temperatures in an embodiment of the present disclosure. DETAILED DESCRIPTION

[0034] The following is an explanation of the implementation of the present disclosure by means of specific embodiments. People familiar with the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification.

[0035] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0036] In addition, it should be understood that one or more method steps mentioned in the present disclosure do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present disclosure does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present disclosure without substantially changing the technical content.

[0037] In the related technology, high-performance lubricating coatings mainly use polyethersulfone, polyimide and the like as film-forming materials, and the curing temperature is higher than 200°C. High-temperature treatment can easily lead to oxidation and discoloration of the bearings. In addition, due to the lack of active groups on the surface of the lubricating material and poor compatibility with other inorganic fillers and organic resins, the coating's density, lubricity, wear resistance and other properties are impaired, thereby affecting the structural mechanics of the bearing body and reducing the service life of the equipment.

[0038] In order to solve the technical problems in the related art, a low-temperature curing lubricating coating for a fan bearing is provided in an embodiment of the present disclosure. The low-temperature curing lubricating coating for a fan bearing includes the following components in parts by weight: 55 to 65 parts of a mixed solvent, 10 to 15 parts of a composite bonding resin, 10 to 15 parts of a modified lubricating filler, 8 to 12 parts of a wear-resistant filler, 0.5 to 3 parts of a dispersant, 0.5 to 1 part of micronized dicyandiamide, 0.5 to 2 parts of a leveling agent, 0.5 to 2 parts of a defoaming agent, and 0.5 to 1 part of an anti-settling agent; wherein the composite bonding resin includes the following components in parts by weight: 10 to 20 parts of a silicone resin, 15 to 30 parts of a phenolic epoxy resin, 15 to 30 parts of a polyurethane acrylate, and 35 to 45 parts of a polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene.

[0039] Next, the low-temperature curing lubricating coating for fan bearings in the embodiment of the present disclosure is described in detail.

[0040] In the embodiment of the present disclosure, the mixed solvent includes the following components in parts by weight: 35-45 parts of xylene, 1-5 parts of n-butyl acetate, 15-25 parts of ethylene glycol ethyl ether acetate, 20-30 parts of 2-butoxyethanol, 1-5 parts of benzyl alcohol, 5-10 parts of n-butanol, and 1-3 parts of 2-propanol.

[0041] The mixed solvent is composed of 35-45 parts of xylene, 1-5 parts of n-butyl acetate, 15-25 parts of ethylene glycol ethyl ether acetate, 20-30 parts of 2-butoxyethanol, 1-5 parts of benzyl alcohol, 5-10 parts of n-butanol and 1-3 parts of 2-propanol in parts by weight.

[0042] In the disclosed embodiment, the composite bonding resin includes the following components by weight: 10-20 parts of silicone resin, 15-30 parts of phenolic epoxy resin, 15-30 parts of polyurethane acrylate, and 35-45 parts of polyhydroxy polyether resin. The molecular weight of the polyhydroxy polyether resin is 30,000-50,000. Since the polyhydroxy polyether resin contains a large number of hydroxyl groups, it has excellent adhesion to the surface of the substrate, which is conducive to improving the adhesion ability of the lubricating coating.

[0043] Optionally, the composite bonding resin is composed of 15 parts of silicone resin, 20 parts of phenolic epoxy resin, 25 parts of polyurethane acrylate and 40 parts of polyhydroxy polyether resin in parts by weight.

[0044] In the embodiment of the present disclosure, the wear-resistant filler includes aluminum tripolyphosphate, fumed silica and titanium dioxide, and the weight ratio of aluminum tripolyphosphate, fumed silica and titanium dioxide is 1:2:2, that is, the wear-resistant filler is composed of aluminum tripolyphosphate, fumed silica and titanium dioxide in a weight ratio of 1:2:2. Among them, the aluminum tripolyphosphate is 400-800 mesh, the fumed silica is 15-30 nm, and the titanium dioxide is a nano-assembly structure, which is agglomerated from 400-800 nm particles into 3-5 μm.

[0045] In the disclosed embodiment, the dispersant is at least one of a copolymer solution having an acidic group, a high molecular weight block copolymer solution containing a pigment affinity group, and a styrene maleic anhydride copolymer.

[0046] Optionally, the dispersant is styrene maleic anhydride copolymer, and the added amount is 0.5 to 1 part.

[0047] In the disclosed embodiment, the amount of micronized dicyandiamide is 0.5 to 1 part.

[0048] Optionally, the low-temperature curing lubricating coating for fan bearings includes 0.6 parts by weight of micronized dicyandiamide.

[0049] In the disclosed embodiment, the leveling agent is selected from polyether-modified polydimethylsiloxane.

[0050] In the disclosed embodiment, the defoaming agent is selected from foam-breaking polysiloxane.

[0051] In the disclosed embodiment, the anti-settling agent is selected from a combination of organic bentonite and polyamide wax, with a mass ratio of 1:0.5 to 1:2.

[0052] In the disclosed embodiment, the modified lubricating filler is prepared by the following steps:

[0053] 1) Molybdenum disulfide and polytetrafluoroethylene are mixed in a preset mass ratio to obtain a mixed powder containing molybdenum disulfide and polytetrafluoroethylene, and the mixed powder is treated by dielectric barrier discharge plasma technology.

[0054] 2) The treated mixed powder is ultrasonically dispersed in an ethanol solution, a preset mass of a modifier is added, and the mixture is reacted at room temperature for 8 to 24 hours, and then the modified lubricating filler is obtained after centrifugation, washing and drying.

[0055] Wherein, the preset mass ratio of step 1) is 1:1-4:1, that is, molybdenum disulfide and polytetrafluoroethylene are mixed in a mass ratio of 1:1-4:1 to obtain a mixed powder containing molybdenum disulfide and polytetrafluoroethylene.

[0056] The particle size of molybdenum disulfide in step 1) is 3~7 μm, and the particle size of polytetrafluoroethylene is 500 nm~3 μm.

[0057] In step 2), the treated mixed powder is ultrasonically dispersed in a 90% ethanol solution.

[0058] In order to obtain the best modification effect, the mixed powder was modified after being treated with dielectric barrier discharge plasma for 30 min~5 h.

[0059] Dielectric Barrier Discharge (DBD) is a gas discharge technology that inserts an insulating medium into the discharge space. This technology applies a sufficiently high AC voltage to the discharge electrodes to cause the gas between the electrodes to be broken down to form the so-called dielectric barrier discharge. The characteristics of DBD are non-thermal equilibrium discharge under high gas pressure, and the discharge process is uniform and stable. Specifically, the basic structure of DBD includes electrodes, dielectric layers and discharge gaps. When high voltage is applied to both ends of the electrodes, the gas near the cathode will be ionized and generate electrons under the action of the electric field. These electrons are accelerated in the electric field to form an electron avalanche. Due to the existence of the dielectric layer, the current is confined to the micro-discharge channel, forming a fast pulse discharge filament current. This discharge process is composed of a large number of tiny fast pulse discharge channels, each of which is equivalent to a single streamer breakdown, the so-called micro-discharge.

[0060] In the disclosed embodiment, the discharge gap width of the dielectric barrier discharge plasma technology is 8 mm, the voltage is 30 kV, the gas flow rate is 20-50 mL / min, the gas is a mixture of oxygen and water vapor obtained by bubbling, and the treatment time is 4-8 h.

[0061] In the embodiment of the present disclosure, the modifier is a combination of a first modifier, a second modifier and a third modifier.

[0062] Among them, the addition amount of the first modifier is 3%~5% of the total mass of the mixed powder containing molybdenum disulfide and polytetrafluoroethylene, the addition amount of the second modifier is 1%~2% of the total mass of the powder, and the addition amount of the third modifier is 0.2%~0.5% of the total mass of the powder.

[0063] Optionally, the first modifier is selected from silane coupling agent modifiers, the third modifier is selected from dodecyltrimethylammonium chloride, and the second modifier is selected from thiol (-SH) containing modifiers having the following structure:

[0064]

[0065] Wherein, m and n are independent of each other, n is a natural number selected from 3 to 5, and m is a natural number selected from 1 to 3.

[0066] The Si-OH produced by the hydrolysis of the first modifier can undergo a grafting reaction with the active groups on the surface of the lubricating powder, the second modifier can be thiol-modified at the sulfur atom missing sites of molybdenum disulfide, and the third modifier can be adsorbed on the surface of the lubricating powder to physically adsorb and modify the chemically unmodified sites. At the same time, the polar groups at the ends of the first and second modifiers can enhance the compatibility with polar resins, and the third modifier increases the steric hindrance between the particles to avoid filler agglomeration. Therefore, by adding a preset mass of modifiers to the mixed powder treated with dielectric barrier discharge plasma technology and reacting at room temperature, the interfacial compatibility between the lubricating filler and the remaining components of the coating can be effectively improved, so that the lubricating coating has a compact structure and excellent adhesion, wear resistance and lubrication properties.

[0067] In the technical solution provided in the embodiment of the present disclosure, a lubricating coating comprising a mixed solvent, a composite bonding resin, a modified lubricating filler, a wear-resistant filler, a dispersant, a micronized dicyandiamide, a leveling agent, a defoaming agent and an anti-settling agent is provided. The modified lubricating filler obtained by modifying a mixed powder comprising molybdenum disulfide and polytetrafluoroethylene can effectively improve the interfacial compatibility between the lubricating filler and the remaining components of the coating, making the lubricating coating structure compact. The provided composite bonding resin has the characteristics of high hardness, good wear resistance and low surface friction coefficient, and can effectively improve the wear resistance and lubrication performance of the lubricating coating. The provided composite bonding resin includes a polyhydroxy polyether resin including a large number of hydroxyl groups and has excellent adhesion to the surface of the substrate, thereby improving the adhesion of the coating. The provided mixed solvent has excellent solubility and wettability to the composite bonding resin and filler, and can promote curing, promote leveling, and enhance adhesion, thereby improving the adhesion, wear resistance and lubrication performance of the lubricating coating as a whole, and can effectively protect the structural mechanics of the bearing body. Moreover, compared with related technologies, the curing temperature of the lubricating coating can be lowered, thereby avoiding oxidation discoloration caused by high-temperature treatment of the wind turbine gearbox bearing.

[0068] In an embodiment of the present disclosure, a method for preparing a low-temperature curing lubricating coating for a fan bearing is also provided, comprising sequentially adding a composite bonding resin, a modified lubricating filler, a dispersant, a defoaming agent, a wear-resistant filler, micronized dicyandiamide, a leveling agent, a defoaming agent and an anti-settling agent into a mixed solvent, wherein the defoaming agent is added in two batches successively.

[0069] Specifically, the preparation method of the low temperature curing lubricating coating for fan bearings may include the following steps:

[0070] Step 1), adding a composite adhesive resin to a mixed solvent, and after the composite adhesive resin is completely dissolved, fully dispersing the modified lubricating filler in the mixed solvent, and adding a dispersant and a defoaming agent and stirring to obtain a uniform slurry; wherein the composite adhesive resin comprises the following components by weight: 10 to 20 parts of silicone resin, 15 to 30 parts of phenolic epoxy resin, 15 to 30 parts of polyurethane acrylate, and 35 to 45 parts of polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene.

[0071] Step 2), wear-resistant filler and micronized dicyandiamide are added to the uniform slurry in sequence, stirred evenly, and then ball milled for dispersion treatment, and filtered to obtain filtered slurry.

[0072] Step 3), a leveling agent, a defoaming agent and an anti-settling agent are sequentially added to the filtered slurry and stirred to prepare a low-temperature curing lubricating coating for fan bearings.

[0073] It should be noted that the method for modifying the mixed powder containing molybdenum disulfide and polytetrafluoroethylene to obtain a modified lubricating filler can be referred to the above-mentioned specific embodiments, which will not be described in detail here.

[0074] The process of adding the composite binder resin to the mixed solution until the composite binder resin is completely dissolved can be carried out in a cooling dispersion tank. The specific rotation speed can be set according to actual needs and is not specifically limited. It is necessary to ensure that the composite binder resin can be completely dissolved.

[0075] Optionally, in order to allow the modified lubricating filler to be fully dispersed in the mixed solution, the modified lubricating filler can be added in multiple batches, for example, the modified lubricating filler can be added to the mixed solution in 3 to 5 batches. The number of batches and the amount of modified lubricating filler added in each batch can be selected according to the actual dispersion situation, and there is no limitation on this.

[0076] Optionally, the defoaming agent added for the first time in step 1) may be half of the total amount of the defoaming agent, and the remaining half is added in step 3) to improve the defoaming effect.

[0077] Optionally, the mixture may be stirred for 10 to 15 minutes after the dispersant and defoamer are added to ensure adequate mixing. Preferably, the mixture may be stirred for 15 minutes.

[0078] Optionally, wear-resistant fillers and micronized dicyandiamide are added to the uniform slurry in sequence, and stirred for 25 to 35 minutes, which can be flexibly selected according to actual conditions. After being stirred evenly, it can be transferred to a ball mill for ball milling dispersion for 50 to 70 minutes, and then filtered through a filter screen, and then a leveling agent, a defoaming agent and an anti-settling agent are added for stirring, and stirred for 25 to 35 minutes. It can be stirred in a cooling dispersion tank, and the speed of the cooling dispersion tank is 600 to 800 rpm, which can be set according to actual needs and is not specifically limited to this.

[0079] The solution of the embodiment of the present disclosure is described in detail below through specific examples.

[0080] Example 1

[0081] The steps of preparing the modified lubricating filler in this embodiment include:

[0082] Weigh 10 g of 3-5 μm molybdenum disulfide and 10 g of 500 nm-1 μm polytetrafluoroethylene, mix them evenly in a drum ball mill, place them in a quartz reactor, set the discharge gap width to 8 mm, the voltage to 30 kV, the gas flow rate to 20 mL / min, and the treatment time to 8 h. Ultrasonic disperse the treated mixed powder in 100 mL of 90% ethanol solution, add 0.6 g KH550 (silane coupling agent), 0.4 g -SH modifier, and 0.06 g dodecyltrimethylammonium chloride in sequence, react at room temperature for 12 h, then centrifuge and wash, and dry at 60 °C to obtain the modified lubricating filler for use.

[0083] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0084] 21 g of xylene, 2.4 g of n-butyl acetate, 9 g of ethylene glycol ethyl ether acetate, 18 g of 2-butoxyethanol, 3 g of benzyl alcohol, 4.8 g of n-butanol, 1.8 g of 2-propanol; 1.15 g of silicone resin, 3.45 g of phenolic epoxy resin, 1.73 g of polyurethane acrylate, 5.17 g of polyhydroxy polyether resin; 10 g of modified lubricating filler; 2.4 g of aluminum tripolyphosphate, 4.8 g of fumed silica, 4.8 g of titanium dioxide; 3 g of BYK-163 dispersant; 0.5 g of micronized dicyandiamide; 1 g of BYK-333 leveling agent; 1 g of BYK-066n defoamer; 0.5 g of organic bentonite, and 0.5 g of polyamide wax.

[0085] The steps of preparing the lubricating coating in this embodiment include:

[0086] In a cooling dispersion tank, mix the organic solvents in the raw materials evenly, then add silicone resin, phenolic epoxy resin, polyurethane acrylate and polyhydroxy polyether resin in turn and stir. After the resin is completely dissolved, increase the speed of the high-speed disperser to 1200 rpm, add modified lubricating fillers in three batches, add dispersants and 1 / 2 defoamers after sufficient dispersion and stir for 15 min. Then add aluminum tripolyphosphate, titanium dioxide, fumed silica and micronized dicyandiamide in turn and stir for 30 min. Transfer to a ball mill, ball mill and disperse for 1 h, filter with a 200-mesh filter, add leveling agent, 1 / 2 defoamer, polyamide wax and organic bentonite in turn, and stir at 1500 rpm in a cooling dispersion tank for 30 min.

[0087] Example 2

[0088] The steps of preparing the modified lubricating filler in this embodiment include:

[0089] Weigh 15 g of 5-7 μm molybdenum disulfide and 5 g of 1-3 μm polytetrafluoroethylene, mix them evenly in a drum ball mill, place them in a quartz reactor, set the discharge gap width to 8 mm, the voltage to 30 kV, the gas flow rate to 50 mL / min, and the treatment time to 4 h. Ultrasonic disperse the treated powder in 100 mL of 90% ethanol solution, add 0.8 g KH550, 0.2 g -SH modifier, and 0.1 g dodecyltrimethylammonium chloride in sequence, react at room temperature for 8 h, then centrifuge and wash, and dry at 60 °C to obtain the modified lubricating filler for use.

[0090] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0091] 29.25 g of xylene, 0.65 g of n-butyl acetate, 13 g of ethylene glycol ethyl ether acetate, 13 g of 2-butoxyethanol, 1.95 g of benzyl alcohol, 6.5 g of n-butanol, 0.65 g of 2-propanol; 1.5 g of silicone resin, 2 g of phenolic epoxy resin, 2.5 g of polyurethane acrylate, 4 g of polyhydroxy polyether resin; 12.5 g of modified lubricating filler; 1.6 g of aluminum tripolyphosphate, 3.2 g of fumed silica, 3.2 g of titanium dioxide; 0.5 g of Anjikang 6200B dispersant; 1 g of micronized dicyandiamide; 0.5 g of BYK-333 leveling agent; 2 g of BYK-066n defoamer; 0.15 g of organic bentonite, and 0.35 g of polyamide wax.

[0092] The steps for preparing the lubricating coating in this embodiment can refer to Example 1.

[0093] Example 3

[0094] The steps of preparing the modified lubricating filler in this embodiment include:

[0095] Weigh 16 g of 5-7 μm molybdenum disulfide and 4 g of 800 nm-1.5 μm polytetrafluoroethylene, mix them evenly in a drum ball mill, place them in a quartz reactor, set the discharge gap width to 8 mm, the voltage to 30 kV, the gas flow rate to 35 mL / min, and the treatment time to 6 h. The treated powder was ultrasonically dispersed in 100 mL of 90% ethanol solution, and 1.0 g KH550, 0.2 g -SH modifier, and 0.06 g dodecyltrimethylammonium chloride were added in sequence. The reaction was carried out at room temperature for 24 h, followed by centrifugal washing, and dried at 60 °C to obtain the modified lubricating filler for use.

[0096] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0097] 20.35 g of xylene, 2.75 g of n-butyl acetate, 13.75 g of ethylene glycol ethyl ether acetate, 13.75 g of 2-butoxyethanol, 0.55 g of benzyl alcohol, 2.75 g of n-butanol, 1.1 g of 2-propanol; 3 g of silicone resin, 2.25 g of phenolic epoxy resin, 4.5 g of polyurethane acrylate, 5.25 g of polyhydroxy polyether resin; 15 g of modified lubricating filler; 2 g of aluminum tripolyphosphate, 4 g of fumed silica, 4 g of titanium dioxide; 1 g of BYK-110 dispersant; 1 g of micronized dicyandiamide; 2 g of BYK-333 leveling agent; 0.5 g of BYK-066n defoamer; 0.1 g of organic bentonite, and 0.4 g of polyamide wax.

[0098] The steps for preparing the lubricating coating in this embodiment can refer to Example 1.

[0099] Comparative Example 1

[0100] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0101] 20.35 g of xylene, 2.75 g of n-butyl acetate, 13.75 g of ethylene glycol ethyl ether acetate, 13.75 g of 2-butoxyethanol, 0.55 g of benzyl alcohol, 2.75 g of n-butanol, 1.1 g of 2-propanol; 3 g of silicone resin, 2.25 g of phenolic epoxy resin, 4.5 g of polyurethane acrylate, 5.25 g of polyhydroxy polyether resin; 12 g of 4~7 μm molybdenum disulfide, 3 g of 500 nm~1 μm polytetrafluoroethylene; 2 g of aluminum tripolyphosphate, 4 g of fumed silica, 4 g of titanium dioxide; 1 g of Anjikang 6200B dispersant; 1 g of micronized dicyandiamide; 2 g of BYK-333 leveling agent; 0.5 g of BYK-066n defoamer; 0.1 g of organic bentonite, and 0.4 g of polyamide wax.

[0102] The steps of preparing the lubricating coating in this embodiment include:

[0103] In a cooling dispersion tank, mix the organic solvents in the raw materials evenly, then add silicone resin, phenolic epoxy resin, polyurethane acrylate and polyhydroxy polyether resin in turn and stir. After the resin is completely dissolved, the speed of the high-speed disperser is increased to 1200 rpm, and molybdenum disulfide and polytetrafluoroethylene are added in three batches. After sufficient dispersion, add dispersant and 1 / 2 defoamer and stir for 15 min. Then add aluminum tripolyphosphate, titanium dioxide, fumed silica and micronized dicyandiamide in turn and stir for 30 min. Transfer to a ball mill, ball mill and disperse for 1 h, filter with a 200-mesh filter, add leveling agent, 1 / 2 defoamer, polyamide wax and organic bentonite in turn, and stir at 1500 rpm in a cooling dispersion tank for 30 min.

[0104] Comparative Example 2

[0105] The steps of preparing the modified lubricating filler in this embodiment include:

[0106] Weigh 15 g of 5-7 μm molybdenum disulfide and 5 g of 1-3 μm polytetrafluoroethylene, mix them evenly using a drum ball mill, and ultrasonically disperse them in 100 mL of 90% ethanol solution. Add 1.0 g of KH550, react at room temperature for 8 h, then centrifuge and wash, and dry at 60°C for use.

[0107] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0108] 29.25 g of xylene, 0.65 g of n-butyl acetate, 13 g of ethylene glycol ethyl ether acetate, 13 g of 2-butoxyethanol, 1.95 g of benzyl alcohol, 6.5 g of n-butanol, 0.65 g of 2-propanol; 1.5 g of silicone resin, 2 g of phenolic epoxy resin, 2.5 g of polyurethane acrylate, 4 g of polyhydroxy polyether resin; 12.5 g of modified lubricating filler; 1.6 g of aluminum tripolyphosphate, 3.2 g of fumed silica, 3.2 g of titanium dioxide; 0.5 g of Anjikang 6200B dispersant; 1 g of micronized dicyandiamide; 0.5 g of BYK-333 leveling agent; 2 g of BYK-066n defoamer; 0.15 g of organic bentonite, and 0.35 g of polyamide wax.

[0109] The steps for preparing the lubricating coating in this embodiment can refer to Example 1.

[0110] Comparative Example 3

[0111] The steps of preparing the modified lubricating filler in this embodiment include:

[0112] Weigh 10 g of 3-5 μm molybdenum disulfide and 10 g of 500 nm-1 μm polytetrafluoroethylene, mix them evenly in a drum ball mill, place them in a quartz reactor, set the discharge gap width to 8 mm, the voltage to 30 kV, the gas flow rate to 20 mL / min, and the treatment time to 8 h. Ultrasonic disperse the treated powder in 100 mL of 90% ethanol solution, add 1.0 g KH550 and 0.06 g dodecyltrimethylammonium chloride in sequence, react at room temperature for 12 h, then centrifuge and wash, dry at 60 °C and set aside.

[0113] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0114] 24.2 g of xylene, 2.8 g of n-butyl acetate, 10.3 g of ethylene glycol ethyl ether acetate, 20.6 g of 2-butoxyethanol, 2.1 g of 2-propanol; 2.1 g of silicone resin, 6.3 g of phenolic epoxy resin, 3.1 g of polyurethane acrylate; 10 g of modified lubricating filler; 4.8 g of aluminum tripolyphosphate, 7.2 g of titanium dioxide; 3 g of BYK-163 dispersant; 1 g of BYK-333 leveling agent; 1.5 g of BYK-066n defoamer; 0.5 g of organic bentonite, and 0.5 g of polyamide wax.

[0115] The steps of preparing the lubricating coating in this embodiment include:

[0116] In a cooling dispersion tank, mix the organic solvents in the raw materials evenly, then add silicone resin, phenolic epoxy resin and polyurethane acrylate in turn and stir. After the resin is completely dissolved, the speed of the high-speed disperser is increased to 1200rpm, and the modified lubricating filler is added in three batches. After sufficient dispersion, the dispersant and 1 / 2 defoamer are added and stirred for 15 minutes. Then, aluminum tripolyphosphate and titanium dioxide are added in turn and stirred for 30 minutes. Transfer to a ball mill, ball mill and disperse for 1 hour, filter with a 200-mesh filter, add leveling agent, 1 / 2 defoamer, polyamide wax and organic bentonite in turn, and stir at 1500 rpm in a cooling dispersion tank for 30 minutes.

[0117] Comparative Example 4

[0118] The steps of preparing the modified lubricating filler in this embodiment include:

[0119] Weigh 15 g of 5-7 μm molybdenum disulfide and 5 g of 1-3 μm polytetrafluoroethylene, mix them evenly in a drum ball mill, place them in a quartz reactor, set the discharge gap width to 8 mm, the voltage to 30 kV, the gas flow rate to 50 mL / min, and the treatment time to 4 h. The treated powder was ultrasonically dispersed in 100 mL of 90% ethanol solution, 0.8 g of KH550 was added to react at room temperature for 8 h, then centrifuged and washed and dried at 60 °C to obtain powder A. Repeat the above steps, wherein the modifier is replaced by 0.2 g -SH modifier and 0.1 g dodecyltrimethylammonium chloride, respectively, to obtain powders B and C. Powders A, B, and C are mixed evenly for use.

[0120] The raw materials weighed for preparing the lubricating coating in this embodiment include:

[0121] 29.25 g of xylene, 0.65 g of n-butyl acetate, 13 g of ethylene glycol ethyl ether acetate, 13 g of 2-butoxyethanol, 1.95 g of benzyl alcohol, 6.5 g of n-butanol, 0.65 g of 2-propanol; 1.5 g of silicone resin, 2 g of phenolic epoxy resin, 2.5 g of polyurethane acrylate, 4 g of polyhydroxy polyether resin; 12.5 g of modified lubricating filler; 1.6 g of aluminum tripolyphosphate, 3.2 g of fumed silica, 3.2 g of titanium dioxide; 0.5 g of Anjikang 6200B dispersant; 1 g of micronized dicyandiamide; 0.5 g of BYK-333 leveling agent; 2 g of BYK-066n defoamer; 0.15 g of organic bentonite, and 0.35 g of polyamide wax.

[0122] The steps for preparing the lubricating coating in this embodiment can refer to Example 1.

[0123] Next, the above Examples 1 to 3 and Comparative Examples 1 to 4 were prepared into coatings by spraying for performance testing. The spraying pressure was ≥0.3 MPa, the spray gun caliber was 1 mm, the spraying distance was 20 to 30 cm, the wet film was placed in an oven and cured at 100 to 120 °C for 20 to 30 min, the dry film thickness of the coating was between 13 and 16 μm, and the coating was taken out for performance testing.

[0124] Among them, the performance test includes: using an electron microscope to observe the microscopic morphology of the coating surface; using a Taber tester to test the wear resistance of the coating, with a load of 1 kg, a rotation speed of 60 r / min, and a number of revolutions of 1000; using an MS-M9000 reciprocating friction and wear tester to test the lubricity of the coating, with a friction load of 10 N, a sliding distance of 5 mm, a frequency of 0.5 Hz, and a friction time of 60 min; using an AT-A adhesion tester to test the adhesion between the coating and the substrate; using the finger touch method to test the dry state of the coating surface as one of the factors to determine whether the coating is cured; using the microhardness method to test the micro-Vickers hardness of the coating, with a load of 0.1 kgf and a holding time of 15 s, and the micro-Vickers hardness is also used as one of the factors to determine whether the coating is completely cured. Among them, when the coating surface is dry by the finger touch method, the micro-Vickers hardness and friction coefficient of the coating at different curing temperatures are measured to comprehensively determine whether the coating is completely cured, so that the curing temperature of the coating can be determined.

[0125] Table 1 shows the experimental results of Examples 1-3 and Comparative Examples 1-4.

[0126] Table 1

[0127]

[0128] Among them, in Comparative Example 1, molybdenum disulfide and polytetrafluoroethylene are added in a single-component manner, and are not modified by dielectric barrier discharge plasma technology and modifiers. In Comparative Example 2, although KH550 is added to the mixed powder of molybdenum disulfide and polytetrafluoroethylene for modification, it is not modified by dielectric barrier discharge plasma technology. In Comparative Example 3, no mercapto-containing modifier is added, no polyhydroxy polyether resin is added to the mixed resin, and no fumed silica is added to the wear-resistant filler. In the preparation process of the modified lubricating filler in Comparative Example 4, a powder corresponding to each modifier is obtained by using a modifier respectively, and finally the three powders corresponding to the three modifiers are mixed to use as a modified lubricating filler for preparing a lubricating coating.

[0129] As shown in Table 1, the wear loss of the lubricating coatings of Examples 1 to 3 is less than 12 mg. Figure 1 The actual picture of the lubricating coating of Example 3 after the Taber wear test is shown. The wear amount of the lubricating coatings of Comparative Examples 1 to 4 is more than 14 mg. It can be seen that the lubricating coating of the embodiment of the present disclosure has high wear resistance.

[0130] The friction coefficients of the lubricating coatings of Examples 1 to 3 are less than 0.1, and the friction coefficients of the lubricating coatings of Comparative Examples 1 to 4 are all greater than 0.1. Figure 2 The friction coefficient test diagram of the lubricating coating of Example 2 is shown. Figure 2 The friction coefficient is 0.042. Figure 3 The test graph of the friction coefficient of the lubricating coating of Comparative Example 2 is shown. Figure 3 The friction coefficient is 0.150. It can be seen that the lubricating coating of the embodiment of the present disclosure has a low friction coefficient and has good lubrication ability.

[0131] The adhesion between the lubricating coating and the substrate of Examples 1 to 3 is significantly higher than the adhesion between the lubricating coating and the substrate of Comparative Examples 1 to 4. Figure 4 The adhesion test diagram of the lubricating coating of Example 2 is shown. Figure 4 The adhesion test result is 19.56 Mpa. Figure 5 The adhesion test diagram of the lubricating coating of Comparative Example 1 is shown. Figure 5 The adhesion test result is 8.27 Mpa. Figure 6 The adhesion test diagram of the lubricating coating of Comparative Example 4 is shown. Figure 6 The adhesion test result is 14.04 Mpa. It can be seen that the lubricating coating of the embodiment of the present disclosure has high adhesion to the substrate. It should be noted that the adhesion test diagram also provides the spindle size (such as 20 mm), the pulling rate (such as 0.10 Mpa / s), the range (such as 20.00 Mpa) and the holding time (such as 20 s), which are not specifically introduced in the embodiment of the present disclosure.

[0132] Continuing to refer to Table 1, the surface conditions of the lubricating coatings of various embodiments are shown, wherein the lubricating coatings of Embodiments 1 to 3 all have a uniform and smooth surface. Figure 7 The electron microscope image of the lubricating coating of Example 1 is shown, and the surface of the lubricating coating is uniform and smooth. The surface of the lubricating coating of Comparative Example 1 has a granular feel, the surface of Comparative Example 2 is uniform and smooth, the surface of Comparative Example 3 is uneven, and the surface of Comparative Example 4 is smooth. For example, Figure 8 An electron microscope image of the lubricating coating of Comparative Example 1 is shown. Figure 8 The surface of the lubricating coating includes a plurality of particle protrusions of different sizes. Fig. 9 An electron microscope image of the lubricating coating of Comparative Example 3 is shown. Fig. 9 , the surface of the lubricating coating is in different concave and convex states, that is, the surface is uneven. It can be seen that the surface of the lubricating coating of the embodiment of the present disclosure is uniform and flat. On the one hand, the uniform and flat coating can improve the adhesion and wear resistance of the coating, thereby extending the service life of the coating. On the other hand, it can prevent the fan bearing from having defects such as cracks, scratches, and peeling in uneven parts during operation, thereby aggravating the wear of the bearing.

[0133] From the above, it can be seen that the low-temperature curing lubricating coating for fan bearings of the embodiment of the present disclosure has the following excellent properties:

[0134] 1) Wear resistance: Under the same test conditions, wear resistance is improved by 20%;

[0135] 2) Lubrication: The average friction coefficient is reduced by 0.05, and the comprehensive friction coefficient is reduced by about 50%;

[0136] 3) Adhesion: The adhesion to the substrate (bearing) reaches over 19 MPa, and the performance is improved by 35%.

[0137] As shown in Table 1, the coating hardness of each embodiment is also shown, from which it can be seen that the coating hardness of embodiments 1 to 3 exceeds 40 HV 0.1 , which is significantly higher than the coating hardness of Comparative Examples 1 to 4, indicating that the coating hardness of the lubricating coating of the embodiment of the present disclosure is significantly improved.

[0138] To further explain this, a variety of mixed resins were prepared into coatings by spraying for performance testing. The spraying pressure was ≥0.3 MPa, the spray gun caliber was 1 mm, and the spraying distance was 20-30 cm. The wet film was placed in an oven for curing, and the coating was taken out for performance testing.

[0139] See also Fig.10 The friction coefficient diagrams of various mixed resin coatings are shown in Fig. Fig.10 As shown, the composite bonding resin prepared in the embodiment of the present disclosure ( Fig.10 The friction coefficients of the four mixed resin coatings, namely, the mixed resin shown in FIG. 1 ), phenolic epoxy resin + polyhydroxy polyether resin, silicone resin + phenolic epoxy resin + polyurethane acrylate, and silicone resin + phenolic epoxy resin, vary with time. The mixed adhesive resin coating of the embodiment of the present disclosure has the lowest friction coefficient. Fig.11 The schematic diagram of the micro-Vickers hardness and wear loss of each mixed resin coating is shown in Fig.11 As shown, the micro-Vickers hardness of the coating corresponding to the composite bonding resin prepared in the embodiment of the present disclosure exceeds 35 HV 0.1 , and the wear amount is less than 20 mg. Compared with other mixed resin coatings, it has the dual characteristics of high hardness and good wear resistance.

[0140] It can be seen that the composite bonding resin provided in the embodiment of the present disclosure has the characteristics of high hardness, good wear resistance and low surface friction coefficient, and can effectively improve the wear resistance and lubrication performance of the lubricating coating. The composite bonding resin provided includes a polyhydroxy polyether resin that includes a large number of hydroxyl groups and has excellent adhesion to the substrate surface.

[0141] In addition, the low-temperature curing lubricating coating for fan bearings of the embodiment of the present disclosure can be cured in the range of 100-120°C, which can avoid oxidation discoloration caused by high-temperature treatment of fan gearbox bearings. Fig.12A schematic diagram of testing the dry state of the coating surface of Example 1 by the finger touch method is shown. The coating surface can be rubbed back and forth by a medium (such as a finger). If there is no paint sticking to the medium, it can be preliminarily determined that the coating has been cured.

[0142] Furthermore, Fig.13 The schematic diagram shows the micro-Vickers hardness and friction coefficient of the coating corresponding to the lubricating coating of Example 1 obtained at different curing temperatures, as shown in FIG. Fig.13 As shown in the figure, at 70°C, the coating film is soft and uncured. At 90°C, the micro-Vickers hardness of the coating is only 25.7 HV 0.1 , and at 100~120 ℃, the micro-Vickers hardness of the coating exceeds 40 HV 0.1 And the friction coefficient is the lowest (less than 0.05). As the temperature continues to rise, the micro-Vickers hardness no longer changes, and the friction coefficient increases slightly, indicating that the 100~120 ℃ coating has been completely cured and has the best performance. Therefore, based on the results of the finger-touch method test of the dry state of the coating surface and the measured micro-Vickers hardness and friction coefficient, it can be explained that the curing temperature range of the lubricating coating of the embodiment of the present disclosure is 100~120 ℃. Compared with the high-performance lubricating coatings of the related art, which mainly use polyethersulfone, polyimide, etc. as film-forming materials and have a curing temperature higher than 200 ℃, it can effectively reduce the curing temperature and avoid oxidation discoloration of the bearing body due to high-temperature treatment.

[0143] For example, Fig.14 The schematic diagram shows the results of a tin bronze substrate treated at different temperatures. The surface of the tin bronze substrate has no obvious change when treated at 120°C, and the surface of the tin bronze substrate oxidizes and turns yellow when treated at 200°C. It can be seen that the lubricating coating of the embodiment of the present disclosure can achieve low temperature (100-120°C) curing, which can avoid surface oxidation and discoloration of the substrate.

[0144] In the technical solution provided in the embodiment of the present disclosure, a lubricating coating comprising a mixed solvent, a composite bonding resin, a modified lubricating filler, a wear-resistant filler, a dispersant, a micronized dicyandiamide, a leveling agent, a defoaming agent and an anti-settling agent is provided. The modified lubricating filler obtained by modifying a mixed powder comprising molybdenum disulfide and polytetrafluoroethylene can effectively improve the interfacial compatibility between the lubricating filler and the remaining components of the coating, making the lubricating coating structure compact. The provided composite bonding resin has the characteristics of high hardness, good wear resistance and low surface friction coefficient, and can effectively improve the wear resistance and lubrication performance of the lubricating coating. The provided composite bonding resin includes a polyhydroxy polyether resin including a large number of hydroxyl groups and has excellent adhesion to the surface of the substrate, thereby improving the adhesion of the coating. The provided mixed solvent has excellent solubility and wettability to the composite bonding resin and filler, and can promote curing, promote leveling, and enhance adhesion, thereby improving the adhesion, wear resistance and lubrication performance of the lubricating coating as a whole, and can effectively protect the structural mechanics of the bearing body. Moreover, compared with the related art, the curing temperature of the lubricating coating can be lowered, thereby avoiding oxidation discoloration caused by high temperature treatment of the wind turbine gearbox bearing. In summary, the embodiments of the present disclosure overcome the shortcomings of the lubricating coating in the related art and have high industrial utilization value.

[0145] In the embodiments of the present disclosure, a method for applying a low-temperature curing lubricating coating for a fan bearing is also provided. The low-temperature curing lubricating coating for a fan bearing of the above exemplary embodiment is applied to a fan gearbox bearing. As a lubricant, it can effectively reduce the mechanical wear of the bearing, increase the service life of the equipment, and avoid oxidation problems caused by high-temperature treatment. Of course, it should be understood that the low-temperature curing lubricating coating for a fan bearing of the embodiment of the present disclosure can also be applied to other scenarios where mechanical wear needs to be reduced by a lubricant, including but not limited to the application of fan gearbox bearings, other industrial equipment or electronic equipment, and there is no specific limitation on this.

[0146] It should be noted that the above embodiments are only illustrative of the principles and effects of the present disclosure, and are not intended to limit the present disclosure. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present disclosure. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed in the present disclosure should still be covered by the claims of the present disclosure.

Claims

1. A low temperature curing lubricating coating for a fan bearing, characterized in that: The low-temperature curing lubricating coating for fan bearings comprises the following components by weight: 55-65 parts of mixed solvent, 10-15 parts of composite bonding resin, 10-15 parts of modified lubricating filler, 8-12 parts of wear-resistant filler, 0.5-3 parts of dispersant, 0.5-1 parts of micronized dicyandiamide, 0.5-2 parts of leveling agent, 0.5-2 parts of defoamer, and 0.5-1 parts of anti-settling agent; The composite adhesive resin comprises the following components by weight: 10-20 parts of silicone resin, 15-30 parts of phenolic epoxy resin, 15-30 parts of polyurethane acrylate, and 35-45 parts of polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene; The mixed solvent comprises the following components by weight: 35-45 parts of xylene, 1-5 parts of n-butyl acetate, 15-25 parts of ethylene glycol ethyl ether acetate, 20-30 parts of 2-butoxyethanol, 1-5 parts of benzyl alcohol, 5-10 parts of n-butanol, and 1-3 parts of 2-propanol; the wear-resistant filler comprises aluminum tripolyphosphate, fumed silica and titanium dioxide, and the weight ratio of the aluminum tripolyphosphate, fumed silica and titanium dioxide is 1:2:2; The modified lubricating filler is prepared by the following steps: Mixing molybdenum disulfide and polytetrafluoroethylene at a preset mass ratio to obtain the mixed powder containing molybdenum disulfide and polytetrafluoroethylene, and treating the mixed powder by dielectric barrier discharge plasma technology; Ultrasonic dispersion of the treated mixed powder in an ethanol solution, adding a preset mass of a modifier and reacting at room temperature for 8 to 24 hours, centrifuging, washing and drying to obtain the modified lubricating filler; Wherein, the modifier is a combination of a first modifier, a second modifier and a third modifier; the first modifier, the second modifier and the third modifier are sequentially added to the ethanol solution containing the mixed powder of molybdenum disulfide and polytetrafluoroethylene; The amount of the first modifier added is 3% to 5% of the total mass of the mixed powder containing molybdenum disulfide and polytetrafluoroethylene, the amount of the second modifier added is 1% to 2% of the total mass of the powder, and the amount of the third modifier added is 0.2% to 0.5% of the total mass of the powder; The first modifier is selected from a silane coupling agent modifier, the second modifier is selected from a thiol-containing modifier having the following structure, and the third modifier is selected from dodecyltrimethylammonium chloride, ; Wherein, m and n are independent of each other, n is a natural number selected from 3 to 5, and m is a natural number selected from 1 to 3.

2. The low temperature curing lubricating coating for fan bearings according to claim 1, characterized in that: The curing temperature range of the low-temperature curing lubricating coating for fan bearings is 100-120°C.

3. The low temperature curing lubricating coating for fan bearings according to claim 1 is characterized in that: The preset mass ratio refers to a mass ratio of the molybdenum disulfide to the polytetrafluoroethylene of 1:1 to 4:

1.

4. The low temperature curing lubricating coating for fan bearings according to claim 1, characterized in that: The particle size of the molybdenum disulfide is 3-7 μm, and the particle size of the polytetrafluoroethylene is 500 nm-3 μm.

5. The low temperature curing lubricating coating for fan bearings according to claim 1, characterized in that: The dielectric barrier discharge plasma technology has a discharge gap width of 8 mm, a voltage of 30 kV, a gas flow rate of 20-50 mL / min, a gas that is a mixture of oxygen and water vapor obtained by bubbling, and a treatment time of 4-8 h.

6. A method for preparing a low-temperature curing lubricating coating for a fan bearing, used for preparing a low-temperature curing lubricating coating for a fan bearing as claimed in any one of claims 1 to 5, characterized in that: include: Add a composite adhesive resin to a mixed solvent, wait for the composite adhesive resin to be completely dissolved, fully disperse the modified lubricating filler in the mixed solvent, add a dispersant and a defoaming agent and stir to obtain a uniform slurry; wherein the composite adhesive resin comprises the following components by weight: 10-20 parts of silicone resin, 15-30 parts of phenolic epoxy resin, 15-30 parts of polyurethane acrylate, and 35-45 parts of polyhydroxy polyether resin; the modified lubricating filler is obtained by modifying a mixed powder containing molybdenum disulfide and polytetrafluoroethylene; Adding wear-resistant filler and micronized dicyandiamide to the uniform slurry in sequence, stirring evenly, performing ball milling dispersion treatment, and filtering to obtain filtered slurry; Adding a leveling agent, a defoaming agent and an anti-settling agent to the filtered slurry in sequence and stirring the mixture to prepare a low-temperature curing lubricating coating for a fan bearing; The mixed solvent comprises the following components by weight: 35-45 parts of xylene, 1-5 parts of n-butyl acetate, 15-25 parts of ethylene glycol ethyl ether acetate, 20-30 parts of 2-butoxyethanol, 1-5 parts of benzyl alcohol, 5-10 parts of n-butanol, and 1-3 parts of 2-propanol; the wear-resistant filler comprises aluminum tripolyphosphate, fumed silica and titanium dioxide, and the weight ratio of the aluminum tripolyphosphate, fumed silica and titanium dioxide is 1:2:2; The modified lubricating filler is prepared by the following steps: Mixing molybdenum disulfide and polytetrafluoroethylene at a preset mass ratio to obtain the mixed powder containing molybdenum disulfide and polytetrafluoroethylene, and treating the mixed powder by dielectric barrier discharge plasma technology; Ultrasonic dispersion of the treated mixed powder in an ethanol solution, adding a preset mass of a modifier and reacting at room temperature for 8 to 24 hours, centrifuging, washing and drying to obtain the modified lubricating filler; Wherein, the modifier is a combination of a first modifier, a second modifier and a third modifier; the first modifier, the second modifier and the third modifier are sequentially added to the ethanol solution containing the mixed powder of molybdenum disulfide and polytetrafluoroethylene; The amount of the first modifier added is 3% to 5% of the total mass of the mixed powder containing molybdenum disulfide and polytetrafluoroethylene, the amount of the second modifier added is 1% to 2% of the total mass of the powder, and the amount of the third modifier added is 0.2% to 0.5% of the total mass of the powder; The first modifier is selected from a silane coupling agent modifier, the second modifier is selected from a thiol-containing modifier having the following structure, and the third modifier is selected from dodecyltrimethylammonium chloride, ; Wherein, m and n are independent of each other, n is a natural number selected from 3 to 5, and m is a natural number selected from 1 to 3.

Citation Information

Patent Citations

  • Aqueous coating agent composition and aqueous coating composition comprising same for lubricating film

    CN111032803A

  • Coating with good lubricating performance and coating process thereof

    CN111234661A